Marasmus and stunting in 2-month-old boy with pneumatocele - Susanti, Maya; Juliaty, Aidah (Faculty of Medicine, Universitas Trisakti, 2021)
BackgroundNutrition is essential for humans and if inadequate may lead to undernutrition. Undernourished children are very susceptible to infections, such as pneumonia, one of its complications being pneumatocele, which is a more severe condition. Pulmonary pneumatoceles are thin-walled, air-filled cysts that develop within the lung parenchyma and have been found in 2.4 percent of 493 infants and children with pneumonia. However, in staphylococcal pneumonias, the frequency of pneumatocele can reach as high as 85 percent. Infants and young children are more likely to have pneumatoceles. It is critical to distinguish marasmus with pneumatocele from many other similar diagnoses. Failure to recognize can lead to incorrect diagnosis and treatment, causing more harm than good to patient care. This case highlights the importance of maintaining a high suspicion of pneumonia in neonates even with normal radiological findings and of searching for pneumatoceles. Case DescriptionWe report a case of marasmus and stunting accompanied by pneumatocele in a 2-month-old boy. The diagnosis was made based on history, physical examination, anthropometric examination using the WHO child growth standards, laboratory tests, and radiological imaging. Management of the patient was according to a multidisciplinary system including antibiotics administration and wasting management. ConclusionPneumatoceles are serious complications after pneumonia. Pneumonia is common in children with marasmus. Children with marasmus are caused by various underlying factors. The progression begins in the womb and continues through the first 1000 days of life.